Analisis Kebijakan Pendidikan Diniyah dalam Implementasi Kurikulum Madrasah Diniyah di Lingkungan Pesantren - Imam Fahrurrozi; Imam Baihaki; Miftakhul Qurrota A’yun; Ardianto Ardianto (At Tadbir: Islamic Education Management Journal, 2024)
This research aims to analyze the Islamic education policy in implementing the Madrasah Islamic curriculum in the Islamic boarding school environment. The main focus of the research is to analyze the early education gap, adaptive early education curriculum, obstacles to early curriculum development and sustainable early education models. A qualitative approach is used with the case study method. Data was obtained through in-depth interviews, observation, and review of related documents. The research results show that there is a gap between the early education policy and the needs of traditional Islamic boarding schools, especially in maintaining local characteristics such as the yellow book curriculum. Islamic boarding schools face challenges in infrastructure, funding and human resource training, which hinder curriculum innovation. Manbaul Ulum Islamic Boarding School has combined religious values ??with modern skills, despite being constrained by technology and resources. This research proposes a sustainable, technology-based model of early education, teacher training, and collaboration with the business world to produce adaptive and relevant graduates without losing Islamic identity.